2010
DOI: 10.3390/ijms11041365
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dietary Polyphenols on Carbohydrate Metabolism

Abstract: Polyphenols, including flavonoids, phenolic acids, proanthocyanidins and resveratrol, are a large and heterogeneous group of phytochemicals in plant-based foods, such as tea, coffee, wine, cocoa, cereal grains, soy, fruits and berries. Growing evidence indicates that various dietary polyphenols may influence carbohydrate metabolism at many levels. In animal models and a limited number of human studies carried out so far, polyphenols and foods or beverages rich in polyphenols have attenuated postprandial glycem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
656
1
30

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 974 publications
(698 citation statements)
references
References 213 publications
(208 reference statements)
11
656
1
30
Order By: Relevance
“…Moreover, products with low amounts of simple sugars, low glycemic index or rich in fiber can be of interest in the management of blood glucose alterations [22][23][24]. In that context, fruits and fruit-derived products have shown some healthy benefits, improving carbohydrate, lipid profile and, oxidative status [25,26]. However, to date little is known about the effect of the addition of natural antioxidants to fruit-derived products, such as jams.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, products with low amounts of simple sugars, low glycemic index or rich in fiber can be of interest in the management of blood glucose alterations [22][23][24]. In that context, fruits and fruit-derived products have shown some healthy benefits, improving carbohydrate, lipid profile and, oxidative status [25,26]. However, to date little is known about the effect of the addition of natural antioxidants to fruit-derived products, such as jams.…”
Section: Discussionmentioning
confidence: 99%
“…This result was comparable to the inclusion of crude propolis , which showed that pancreatic amylase activity decreased with dietary inclusion of crude propolis, possibly related to the inhibitory effect of propolis polyphenols on amylase and maltase activity (MATSUI et al, 2004;ZHANG et al, 2015), despite the low concentration of these compounds in the residue. Many authors have shown that amylase and maltase activity may be decreased by anthocyanins, phenolic acids, and flavonoids (FORESTER et al, 2012;HANHINEVA et al, 2010;MCDOUGALL et al, 2005). This is due to either non-competitive inhibition associated with the number of hydroxyl groups on the B-ring of the flavonoid skeleton, and consequent formation of hydrogen bonds between the hydroxyl groups of the polyphenol ligands and catalytic site of the enzyme (LO PIPARO et al, 2008), or the antioxidant properties of the polyphenols, which may also inhibit amylase activity (HASHIM et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Flavanols have been shown to inhibit glucosidase and glucose absorption from the intestine, protect pancreatic b cells, increase insulin secretion, activate insulin receptors and glucose uptake in insulin-sensitive tissues, and modulate intracellular signaling pathways and genes involved in gluconeogenesis and glycogenesis (15,52). Flavanols may also improve insulin sensitivity by increasing NO bioavailability and inhibiting production of reactive oxygen species and nitrogen species (5, 6).…”
Section: Discussionmentioning
confidence: 99%